Gender, culture and politics in England, 1560-1640 turning the world upside down - Amussen, Susan D. 1954-; Underdown, David 1925-2009 (Cultures of early modern Europe, 2017)
"Gender, Culture and Politics in England, 1560-1640 integrates social history, politics and literary culture as part of a groundbreaking study that provides revealing insights into the lives of men and women in early modern England. Susan D. Amussen and David E. Underdown examine familiar chaotic characters from the period, such as scolds, cuckolds, witches and scandalous women, and consider the significance of the disorder they create and how they turn the ordered world around them upside down in a very specific, gendered way. Using case studies from theatre, civic ritual and witchcraft, the book demonstrates how the idea of an upside down world, centered on gender inversion, repeatedly permeates the mental world of early modern England. Amussen and Underdown show both how gender was central to understanding society, and the ways in which both unruly women and failed patriarchs were disciplined. In doing so, they give a glimpse of how we can connect different dimensions of early modern society. This is a vital study for anyone keen to know more about the importance of gender in society, culture and politics in 16th- and 17th-century England"...Provided by publisher